The Role of Mangrove Vegetation in Supporting Birdlife Diversity in Coastal Habitats, Study Case Benoa, Bali - Christy Shanie Avissa Nathanya; Saptarini Dian (BIO Web of Conferences)
The mangrove ecosystem plays a critical role in maintaining biodiversity, particularly in supporting bird species diversity within coastal habitats by offering essential resources such as nesting sites, shelter, and food. This study analyzes the relationship between mangrove characteristics and the species composition of birds in coastal Benoa areas to explore the role of mangroves in Ngurah Rain Forest Park in supporting bird diversity. Point counts and line transects were utilized to obtain data to observe bird communities, and plot sampling was used to evaluate the characteristics of the mangrove vegetation, including species composition, tree height, and density. Bird diversity was analyzed using the Shannon-Weiner IndexThis study found that the mangrove species identified included Thespesia populnea, Avicennia lanata, A. marina, Rhizophora apiculate, R. stylosa, R. mucranata, Sonneratia alba, Xylocarpus granatum, Aegiceras corniculatum, Ceriops tagal, and Lumnitzera racemose. The observations revealed that at least 21 species of avifauna were identified, including 13 migratory bird species, 7 bird species protected by Minister of Environment and Forestry Regulation No. 106 Year 2018, and two endemic bird species, the bar-winged prinia ( Prinia familiaris) and the blue kingfisher ( Alcedo coerulescens). By examining various sites with differing mangrove structures, this research provides insights into how specific vegetation features influence bird species richness and distribution